Dichotomic problem of dynamic programming for the strictly convex functions. III - Bistrickas, V. (Lithuanian Mathematical Journal, 1969)
The abstracts (in two languages) can be found in the pdf file of the article.Original author name(s) and title in Russian and Lithuanian:В. Б. Бистрицкас. Дихотомическая задача динамического программирования для строго выпуклых функции. IIIV. Bistrickas. Dichotominis dinaminio programavimo uždavinys griežtai iškiloms funkcijoms. III